Efficacy of Median Nerve Mobilization Versus Upper Trapezius Muscle Stretching on Extensibility of Median Nerve in Young Healthy Individuals: A Randomized Controlled Trial - Shiril R. Nagarkar1 , Varsha S. Nagarkar2 , Divya V. Bagaria3 , Vasant Gawande4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective: The purpose of this study was to compare the effect of upper trapezius muscle stretching andmedian nerve mobilization on median nerve extensibility.Design: A randomized controlled trial. Participants: 80 healthy participants with mean age range () wererandomized to two groups who received trapezius muscle stretching & median nerve mobilization.Outcome Measures: Right and left Elbow Extension Deficit Angle (EEDA) in degrees.Intervention: Passive stretching of upper trapezius was done 4 times per week, 3 repetitions, 30 sec holdbilaterally. Median nerve mobilization was done 4 times per week, 3 sets of 10 cycles each; 30 sec rest inbetween bilaterally. Supervised self stretching and nerve mobilization was done 3 times per week, withnumber of hold and repetitions being the same.Results: Baseline characteristics including demographic, anthropomorphic and EEDA between groupswere comparable. Intragroup comparison of right and left Elbow Extension Deficit Angle (EEDA) weredone using Repeated Measure Multivariate ANOVA. Inter group comparison was done using post hoc testBonferroni. The level of significance was set at P < 0.05.Conclusion: The study concludes that Upper trapezius muscle stretching is effective in improving mediannerve extensibility. Both treatment techniques are equally effective.